2018
DOI: 10.21037/gs.2018.03.06
|View full text |Cite
|
Sign up to set email alerts
|

“Super-active surveillance”: MRI ultrasound fusion biopsy and ablation for less invasive management of prostate cancer

Abstract: Multiparametric magnetic resonance imaging (mpMRI) of the prostate has allowed clinicians to better visualize and target suspicious lesions during biopsy. Targeted prostate biopsies give a more accurate representation of the true cancer volume and stage so that appropriate treatment or active surveillance can be selected. Advances in technology have led to the development of MRI and ultrasound fusion platforms used for targeted biopsies, monitoring cancer progression, and more recently for the application of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…For certain well selected patients, the prospect of focal therapy in place of radical surgery or active surveillance may be an attractive alternative, or may be an adjunct to active surveillance. 41 At present, the lack of long term oncologic outcomes, imaging and navigation shortcomings, and uncertainties about the clinical efficacy of focal treatment for high grade lesions has led organizations such as the American Urologic Association/ American Society for Radiation Oncology/Society of Urologic Oncology(AUA/ASTRO/SUO) and European Association of Urology (EAU) to recommend against focal therapy as part of standard of care treatment at this time. 29,54 New guidelines and advancements require evidence-based medicine to better study the long term results of focal therapy in the setting of clinical trials or registries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For certain well selected patients, the prospect of focal therapy in place of radical surgery or active surveillance may be an attractive alternative, or may be an adjunct to active surveillance. 41 At present, the lack of long term oncologic outcomes, imaging and navigation shortcomings, and uncertainties about the clinical efficacy of focal treatment for high grade lesions has led organizations such as the American Urologic Association/ American Society for Radiation Oncology/Society of Urologic Oncology(AUA/ASTRO/SUO) and European Association of Urology (EAU) to recommend against focal therapy as part of standard of care treatment at this time. 29,54 New guidelines and advancements require evidence-based medicine to better study the long term results of focal therapy in the setting of clinical trials or registries.…”
Section: Resultsmentioning
confidence: 99%
“…MRI-TRUS fusion guidance platforms have been developed (at the NIH and UCLA) for transrectal ultrasound MRI fusion guidance, but broadly available FLA platforms are not available. 34,41…”
Section: Contemporary Treatments In Prostate Cancer Focal Therapymentioning
confidence: 99%
“…Hwang et al found that fusion biopsy improved the detection rate of carcinoma in patients with prostate‐specific antigen levels of less than 10 ng/mL. All of these methods allow patients to choose focal therapy combined with active surveillance rather than higher‐risk invasive surgical or radiation therapy procedures for low‐ to intermediate‐risk carcinomas that are contained within the prostate capsule …”
mentioning
confidence: 99%
“…Some are calling “super-active surveillance” a partial gland ablation (22), we don't necessarily agree this might be the precise term. However, we do with the notion that alternatives are needed to fill the gap between the yin and yang - traditional AS vs. radical treatment.…”
mentioning
confidence: 99%